2001
DOI: 10.1021/bm010112y
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Biocompatibility Studies of Novel Humic Acids Based Films as Membrane Material for an Implantable Glucose Sensor

Abstract: Multilayered films of humic acids (HAs) (naturally occurring biopolymers) were investigated as a potential semipermeable membrane for implantable glucose sensors. These films were grown using a layer-by-layer self-assembly process of HAs and oppositely charged ferric ions. The growth of these assemblies exhibited strong dependence on the pH and ionic strength of HAs solutions, which correlated with the degree of ionization of the carboxyl groups and neutralization-induced surface spreading. Quartz crystal micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
57
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(58 citation statements)
references
References 43 publications
1
57
0
Order By: Relevance
“…In general, more hydrophilic polymers such as phosphorylcholine [315,349,350], 2-methacryloxyethyl phosphorylcholine [351][352][353], PEG [354], cross-linked PEG [355], PEG introduced into a hydroxyethylmethacrylate and ethylene dimethacrylate chain, polyvinyl alcohol [356] and water-rich hydrogels [357] have been reported more recently to reduce protein adsorption on sensor surfaces and thereby mitigate the foreign body reaction. Less frequently, hyaluronic acid [358][359][360][361] and humic acid [358] have been utilized in outer biocompatible coatings. Turning to surface morphology, the impact of introducing porosity into biocompatible coatings onto function of implanted glucose sensors has been investigated by several groups [315,[362][363][364][365][366][367].…”
Section: Biocompatible Coatingmentioning
confidence: 99%
“…In general, more hydrophilic polymers such as phosphorylcholine [315,349,350], 2-methacryloxyethyl phosphorylcholine [351][352][353], PEG [354], cross-linked PEG [355], PEG introduced into a hydroxyethylmethacrylate and ethylene dimethacrylate chain, polyvinyl alcohol [356] and water-rich hydrogels [357] have been reported more recently to reduce protein adsorption on sensor surfaces and thereby mitigate the foreign body reaction. Less frequently, hyaluronic acid [358][359][360][361] and humic acid [358] have been utilized in outer biocompatible coatings. Turning to surface morphology, the impact of introducing porosity into biocompatible coatings onto function of implanted glucose sensors has been investigated by several groups [315,[362][363][364][365][366][367].…”
Section: Biocompatible Coatingmentioning
confidence: 99%
“…The manifold number of analyte-membrane/receptor combinations possible with a label-free piezoelectric sensor is apparent from diverse types of measurements reported for a range of analytes. Selected examples include interactions of membranes with tannins (Kaneda et al, 2002b(Kaneda et al, , 2003b, divalent non-metallic cations (Ekeroth et al, 2002), metal ions (Bukreeva et al, 2003), metal-binding proteins , lipases (Pastorino and Nicolini, 2002;Snabe and Petersen, 2003;Justesen et al, 2004), lectins (Hildebrand et al, 2002), Shiga toxin (Uzawa et al, 2002), glucose (Galeska et al, 2001;Svobodová et al, 2002), beer (Kaneda et al, 2002a(Kaneda et al, , 2005, coffee (Kaneda et al, 2003a) and detergents (Shimomura et al, 2003).…”
Section: Lipids and Membranesmentioning
confidence: 99%
“…2 Following device implantation, this is further compounded by inflammation, biofouling, and fibrotic encapsulation, which lead to additional variations in glucose-to-oxygen ratios. [1][2][3][4][5][6] While a number of semipermeable membranes have been developed to optimize the glucose-to-oxygen ratio, [7][8][9][10][11][12][13][14][15][16][17][18] only a few systems have been used with drugreleasing hydrogels, 17,18 designed to suppress inflammation, biofouling, and fibrotic encapsulation. The typical approach to counter both these issues is the use of overlaid membranes in which the inner membrane limits glucose diffusion and the outer membrane counters fibrotic encapsulation.…”
mentioning
confidence: 99%
“…19 In order to reduce membrane thickness and fine-tune permeability, we have employed layer-by-layer (LBL) assemblies based on charged polymers and/or multivalent cations (i.e., Fe 3+ ). 7,11,12,21 In particular, the combination of five humic acid (HA)/Fe 3+ bilayers has been shown to enhance linearity while at the same time reducing sensor response time through the facile outer diffusion of H 2 O 2 . 21 In a separate development, our group has shown that poly(vinyl alcohol) (PVA) hydrogels containing dexamethasone-loaded poly(lactic-co-glycolic acid) microspheres are capable of suppressing inflammation in excess of 1 month.…”
mentioning
confidence: 99%
See 1 more Smart Citation